2021
DOI: 10.1136/injuryprev-2021-044322
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging data science to enhance suicide prevention research: a literature review

Abstract: ObjectiveThe purpose of this research is to identify how data science is applied in suicide prevention literature, describe the current landscape of this literature and highlight areas where data science may be useful for future injury prevention research.DesignWe conducted a literature review of injury prevention and data science in April 2020 and January 2021 in three databases.MethodsFor the included 99 articles, we extracted the following: (1) author(s) and year; (2) title; (3) study approach (4) reason fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…(17) In contrast, a study of call center employees found that 54.6% of them reported having a burning sensation, indicating a high prevalence of the condition. (18) The length of time spent using a computer is directly related to eye symptoms; longer sessions often lead to complaints that persist even after the work is completed. In our study, we discovered a direct relationship between computer use time (including time on a laptop and a mobile device) and computer vision syndrome symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…(17) In contrast, a study of call center employees found that 54.6% of them reported having a burning sensation, indicating a high prevalence of the condition. (18) The length of time spent using a computer is directly related to eye symptoms; longer sessions often lead to complaints that persist even after the work is completed. In our study, we discovered a direct relationship between computer use time (including time on a laptop and a mobile device) and computer vision syndrome symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Responding to this difficulty, machine learning algorithms—models that are designed to predict rare events—are increasingly used to derive complex networks of potential risk variables (Walsh et al, 2017). While related innovations have led to predictive gains, leading suicide prediction models have been critiqued for lacking optimal accuracy and population relevance (Belsher et al, 2019; Kessler, Bossarte, et al, 2019), small sample sizes, restricted potential risk variables, non‐appropriate analytic techniques, lack of clinical implications and ability to compare novel and existing methods (Kessler, 2019; Tsui et al, 2021; Wulz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Social media has the potential to support the early detection of suicide risk. Studies have shown that suicidal thoughts and behaviors can be detected from texts from social media (Ramirez-Cifuentes et al, 2020; Robinson et al, 2016; Tadesse et al, 2020; Wulz et al, 2021). Most AYAs, regardless of gender, socioeconomic status, or race and ethnicity, have access to a computer or own a smartphone to use the internet daily.…”
Section: Introductionmentioning
confidence: 99%